Transformational Leadership in Post-merger Organizations: A Qualitative Study of Indonesian State-owned Company - Raden Moch Ismail Ali Fauzi; Nayunda Andhika Sari (International Journal of Business and Management Technology in Society, 2025)
Purpose – To explore employees’ perceptions of transformational leadership in a post-merger context and to understand the strategies they use to cope with merger-related challenges. Methodology – This study employs a qualitative research design, conducted through semi-structured interviews with ten employees from various hierarchical levels at a company formed from the merger of two major Indonesian state-owned enterprises (BUMN). The qualitative approach is used to capture employees’ subjective interpretations of transformational leadership and their strategies in responding to post-merger challenges. Findings – The study identifies nine key themes across three areas. Employees perceive transformational leadership post-merger as the leader’s ability to orchestrate organizational change, act as a role model, and provide guidance and emotional support during adaptation. They face major challenges including unclear structures and work systems, cultural differences between the merged entities, and a gap between management expectations and operational realities. To navigate these challenges, employees adopt three main strategies: developing acceptance toward organizational changes, demonstrating agility in adjusting roles and decision-making, and strengthening cross-unit and cross-entity collaboration. Originality – This study contributes to the literature on the role of transformational leadership in post-merger organizations and offers practical implications for organizational change management, particularly in the Indonesian context. This study makes an important contribution to the existing literature by presenting a more contextual and in-depth narrative of employees’ experiences in the public sector. In the context of state-owned enterprises, mergers introduce unique complexities because they involve bureaucracy, gaps in work culture, and imbalances in power structures and information.